The Role of Exosomes and Their Cargos in the Mechanism, Diagnosis, and Treatment of Atrial Fibrillation - Huang, Shengyuan; Deng, Yating; Xu, Jiaqi; Liu, Jiachen; Liu, Liming; Fan, Chengming (Frontiers in Cardiovascular Medicine, 2021)
Atrial fibrillation (AF) is the most common persistent arrhythmia, but the mechanism of AF has not been fully elucidated, and existing approaches to diagnosis and treatment face limitations. Recently, exosomes have attracted considerable interest in AF research due to their high stability, specificity and cell-targeting ability. The aim of this review is to summarize recent literature, analyze the advantages and limitations of exosomes, and to provide new ideas for their use in understanding the mechanism and improving the diagnosis and treatment of AF.